Infarct‐like Acute Myocarditis: Relation Between Electrocardiographic Findings and Myocardial Damage as Assessed by Cardiac Magnetic Resonance Imaging. Issue 3 (24th December 2012) - Nucifora, Gaetano; Miani, Daniela; Di Chiara, Antonio; Piccoli, Gianluca; Artico, Jessica; Puppato, Michela; Slavich, Gianaugusto; De Biasio, Marzia; Gasparini, Daniele; Proclemer, Alessandro
Abstract Background: Acute myocarditis (AM) may occasionally have an infarct‐like presentation. The aim of the present study was to investigate the relation between electrocardiographic (ECG) findings in this group of patients and myocardial damage assessed by cardiac magnetic resonance imaging (MRI) with the late gadolinium enhancement (LGE) technique. Hypothesis: Myocardial damage may be associated with ECG changes in infarct‐like AM. Methods: Forty‐one consecutive patients (36 males; mean age, 36 ± 12 years) with diagnosis of AM according to cardiac MRI Lake Louise criteria and infarct‐like presentation were included. The relation between site of ST‐segment elevation (STE), sum of STE (sumSTE), time to normalization of STE, and development of negative T wave with the extent of LGE (expressed as % of left ventricular mass [%LV LGE]), was evaluated. Results: Most (80%) patients presented with inferolateral STE; mean sumSTE was 5 ± 3 mm. Normalization of STE occurred within 24 hours in 20 (49%) patients. Development of negative T wave occurred in 28 (68%) patients. Cardiac MRI showed LGE in all patients; mean %LV LGE was 9.6 ± 7.2%. Topographic agreement between site of STE and LGE was 68%. At multivariate analysis, sumSTE (β = 0.42, P < 0.001), normalization of STE >24 hours (β = 0.39, P < 0.001), and development of negative T wave (β = 0.49, P < 0.001) were independently related to %LV LGE. Conclusions: Analysis of the site of STE underestimates the extent of myocardial injury among patients with infarct‐like myocarditis. However, some ECG features (ie, sumSTE, normalization of STE >24 hours, and development of negative T wave) may help to identify patients with larger areas of myocardial damage. The authors have no funding, financial relationships, or conflicts of interest to disclose.